A treasury of aphoristic jewels : the Subhāṣitaratnanidhi of Sa Skya Paṇḍita in Tibetan and Mongolian /: the Subhāṣitaratnanidhi of Sa Skya Paṇḍita in Tibetan and Mongolian. ([2017]) - Sa-skya Paṇḍi-ta Kun-dgaʾ-rgyal-mtshan, 1182-1251
No abstract available